An Integrated Conceptual Model for m-Government Acceptance in Developing Countries: The Case Study of Jordan - Alqaralleh, Bassam A. Y.; Al-Omari, Ahmad H.; Alksasbeh, Malek Zakarya (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Mobile information and communication technology changed how people and businesses can benefit from government public services at any time and from anyplace. The success or failure of mobile government services is becoming more dependent on satisfying the needs and the expectations of both citizens and business organizations. This paper reviews and analyses some existing empirical studies that examine m-Government acceptance in some developing countries. Then, a new integrated conceptual model for examining some important key factors that may affect m-Government acceptance in Jordan from user perspective was proposed. An empirical test was conducted using a questionnaire to explore the effect of the following factors: Trust in mobile channel, trust in government, perceived usefulness, perceived ease of use, relative advantage, compatibility, complexity, service quality and user satisfaction on the behavioural intention to use m-Government applications. Finally, justification of the proposed integrated model and formulation of the associated hypotheses was conducted.